Take the First Step: Embrace Diversity. Issue 10 (1st October 2013) - Collins, Heather
Abstract : The water industry consists of a vast array of people, manufacturers, partners, and communities. Working with people whose backgrounds and languages are different from yours can expand your cultural awareness and enrich your appreciation for the industry. We are all unified by the same thing ‐ water.